Rationalization of electrocatalysis of nickel phosphide nanowires for efficient hydrogen production - Chung, Young-Hoon; Gupta, Kapil; Jang, Jue-Hyuk; Park, Hyun S.; Jang, Injoon; Jang, Jong Hyun; Lee, Yong-Kul; Lee, Seung-Cheol; Yoo, Sung Jong (ELSEVIER, 2016)
Although the electrochemical hydrogen evolution reaction (HER) has been intensively investigated for decades as a promising hydrogen production source, its economic feasibility is still questionable because of the high cost of Pt-based electrocatalysts. Transition metal phosphides are potential replacements for Pt; however, a fundamental understanding of the active catalyst site chemistry is still lacking. Such an understanding is crucial to design robust catalytic materials. The aim of this study is to rationalize the HER on the active sites of nickel phosphide (Ni2P) nanowires. Using experimental and theoretical analyses, it can be concluded that the active site of Ni2P nanowires is an exposed Ni3P2 surface generated by the oxygenated Ni3P_P surface created during the HER. This work is a breakthrough in the efficient design of phosphide-based non-Pt catalysts for electrochemical hydrogen production. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ACTIVE EDGE SITES; ELECTROLYTIC HYDROGEN; EVOLUTION REACTION; NANOPARTICLES; CATALYSTS; GRAPHENE; NANOSHEETS; ADSORPTION; NI2P(001); SURFACE